Introduction to the theory of employment - Robinson, Joan. (London : Macmillan and co., 1937)
The book aims to provide a simplified account of the main principles of the Theory of Employment for students who find that they require some help in assimilating Mr. Keynes' General Theory of Employment, Interest and Money, and the literature which is growing round it.
rpm 20/02/2018
Loans
Keywords: Unemployed; Economics; Money